Evaluation of the Presence of Bacterial and Viral Agents in the Semen of Infertile Men: A Systematic and Meta-Analysis Review Study - Gholami, Mehrdad; Moosazadeh, Mahmood; Haghshenash, Mohammad Reza; Jafarpour, Hamed; Mousavi, Tahoora (Frontiers in Medicine, 2022)
Objectives Infections in the male genitourinary system with bacterial and viral agents may play a significant role in male infertility. These agents usually infect the urethra, seminal vesicles, prostate, epididymis, vas deferens, and testes retrograde through the reproductive system. A meta-analysis review study was performed to evaluate the presence of bacterial and viral agents in the semen of infertile men and its correlation with infertility. Methods Relevant cross-sectional and/or case-control studies were found by an online review of national and international databases (Web of Science, PubMed, Scopus, Science Direct, and Google scholar), and suitable studies were selected. A checklist determined the qualities of all studies. Heterogeneity assay among the primary studies was evaluated by Cochran’s Q test and I2 index (significance level 50%). A statistical analysis was conducted using the Comprehensive Stata ver. 14 package (StataCorp, College Station, TX, United States). Results Seventy-two studies were included in this meta-analysis. Publication bias was compared with Egger’s test, and the impact of each research on overall estimate was evaluated by sensitivity analysis. In 56 studies, the rate of bacterial infections in the semen of infertile men was 12% [95% confidence interval (CI): 10–13]. Also, in 26 case-control studies, the association of infertility in men with bacterial infections was evaluated. The results show that the odds ratio of infertility in men exposed to bacterial infections is 3.31 times higher than that in non-infected men (95% CI: 2.60–4.23). Besides, in 9 studies that examined the prevalence of human papillomavirus (HPV), herpes simplex virus 1 (HSV1), herpes simplex virus 2 (HSV2), and herpes simplex virus 1-2 (HSV1-2) in infertile men, the frequency of these viruses was 15% (95% CI: 9–21). In 6 case-control studies, the association between human cytomegalovirus (HCMV), Cytomegalovirus (CMV), and HPV and male infertility was evaluated. The chance of male infertility due to exposure to these viruses was 2.24 times higher than those without exposure to these viruses (CI 95%: 1.9–4.52). The results show that the chance of infertility in men exposed to bacteria was significantly higher than that in the uninfected population. Conclusion This meta-analysis showed that viral and bacterial infections are a risk factor and could impair male fertility potential. Moreover, our study supports the hypothesis that bacterial and viral infections of the genital tract correlate positively with impairment of sperm quality in the male population.